EFFECT OF WORK STRESS, WORK MOTIVATION, AND WORK ENVIRONMENT TO EMPLOYEE PERFORMANCE PRODUCTION PART - Kristanti, Desi; Pangastuti, Ria Lestari (UNUSA Press, 2019)
This research was conducted to test work stress, work motivation, work environment on employee performance. The research sample was 50 respondents and used a total sampling method. This study uses a quantitative approach, data for this study were obtained through a research questionnaire that was filled out by predetermined respondents. Variables are measured with a Likert scale. Hypothesis testing using SPSS V20 tools with multiple linear regression analysis methods.The findings about the effect of work stress, work motivation, work environment on the performance of employees of UD. Patama Karya city of Kedirir. First, work stress and work motivation have no significant impact on employee performance. Second, the work environment has a significant effect on employee performance. Third, the work stress silmultually variable work motivation and work environment significantly influence employee performance. The results of this study are expected to be the basis for developing new strategies in an effort to improve work stress, work motivation, work environment on employee performance.